Dark vector - Larsen, Ward (David Slaton and Tru Miller novel, 2025)
"In the wilds of Siberia, a top-secret Russian fighter goes missing on a test flight. The Russian Air Force begins a search, oblivious to their error: they are looking in the wrong spot. The pilot, Colonel Maxim Primakov, has crash landed during an attempted defection.The new chief of CIA clandestine operations, David Slaton, wants desperately to find him, but only one man is in a position to reach Primakov--Tru Miller, a rookie operator. Slaton plots a rescue deep inside Russia, not realizing that he will have to outfox the one other man who knows the truth. Victor Dubonin is a general in Russian intelligence. His search for Primakov is deeply personal--and if he doesn't succeed it will cost him his life"--